Utilization of waxy maize modified starch in the production of raisin cookies - Marzan, Paolo Lozano
The goal of the study was to develop an acceptable formulation of raisin cookie with the optimum level of substitution of all-purpose flour with waxy maize modified starch, in order to improve certain attributes of the product and thus may substitute for the typical raisin cookies. Prior to the three main phase, a preliminary study was conducted to narrow down the range of substitution to 65%, 70%, 80%, and 83%, from which the optimum level was selected. The determination of the final range was based from the panel's prefernce for the samples with levels of substitution higher than 60%. This was done in Phase I, wherein the selection was based from the results of the analysis of variance at α=0.05. In Phase II, the optimum level, 70%, was assessed for replicability by sensory evaluation of samples taken from different production runs. The results of ANOVA revealed that no significant difference existed between the sample. The most acceptable formulation and the control were then subjected to rheological and physico-chemical analysis in Phase III. Except for batter viscosity, baking loss and soluble solids, all other parameters showed no significant difference between the two samples.